2019
DOI: 10.1186/s12889-019-7101-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of selected risk factors for non-communicable diseases in Hargeisa, Somaliland: a cross-sectional study

Abstract: Background Non-communicable diseases (NCDs), particularly cardiovascular diseases, diabetes, respiratory conditions and cancers, are the most common causes of morbidity and mortality globally. Information on the prevalence estimates of NCD risk factors such as smoking, low fruit & vegetable intake, physical inactivity, raised blood pressure, overweight, obesity and abnormal blood lipid are scarce in Somaliland. The aim of this study was to determine the prevalence of these selected risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 33 publications
8
21
2
Order By: Relevance
“…The main comorbidities found in the 131 patients with COVID-19 in our study are similar to the findings of other studies done in Africa [10] Although we are limited by the lack of population-based data on the prevalence of diabetes and cardiovascular diseases in males and females in Somalia, the fact that the proportion of female COVID-19 patients with diabetes in our study (48%; 20/42) was higher than males (32/89; 36%) is consistent with a study done in some areas of Somalia in 2016, which found that the prevalence of risk factors such as diabetes was higher in females than males, and CVD was higher among males, and in both sexes, the risk factors increased with age [15]. These findings are also consistent with another study that examined the burden of noncommunicable diseases in sub-Saharan Africa [12].…”
Section: Discussionsupporting
confidence: 91%
“…The main comorbidities found in the 131 patients with COVID-19 in our study are similar to the findings of other studies done in Africa [10] Although we are limited by the lack of population-based data on the prevalence of diabetes and cardiovascular diseases in males and females in Somalia, the fact that the proportion of female COVID-19 patients with diabetes in our study (48%; 20/42) was higher than males (32/89; 36%) is consistent with a study done in some areas of Somalia in 2016, which found that the prevalence of risk factors such as diabetes was higher in females than males, and CVD was higher among males, and in both sexes, the risk factors increased with age [15]. These findings are also consistent with another study that examined the burden of noncommunicable diseases in sub-Saharan Africa [12].…”
Section: Discussionsupporting
confidence: 91%
“…Khat chewing is also a growing concern among Ethiopian universities [39] associated with low academic performance in Ethiopian students [40][41][42]. Khat chewing contributes to the high burden of non-communicable diseases like cardiovascular disorders [43,44]. Khat increases the concurrent use of cigarettes and increases risky sexual behavior [9] which further increases the burden of the Human Immune Deficiency Virus (HIV).…”
Section: Discussionmentioning
confidence: 99%
“…To date, documentation of health system challenges and opportunities for NCD prevention and control is limited in LMICs, and especially in sub-Saharan Africa and fragile and post-conflict settings. Much of the literature on NCDs in sub-Saharan Africa focuses on documenting the prevalence of NCDs and their (multiple) risk factors [10][11][12][13][14][15][16] as well as providing a socioeconomic and gender breakdown for these [17,18]. Increasingly, the comorbidity of NCDs and infectious chronic diseases (such as HIV/AIDS) [19,20] has also been recognized.…”
Section: Introductionmentioning
confidence: 99%